Battle of Kalniškės: a Fragment of the Fight for Freedom - Noreika , Dainius (Genocidas ir rezistencija, 2012)
The article analyses the structure and composition of the partisan division – the company of Jonas Neifalta-Lakūnas [‘Pilot’] – that fought in the Battle of Kalniškės and its role within the context of the Lithuanian resistance against the second Soviet occupation. The direct causes of the battle, its progress and individual stages are discussed. The study uses narrative, analytical and inductive approaches. Lakūnas’ company was part of the partisan forces of several rural areas under the leadership of Albinas Kisieliauskas- Karvelis [‘Pigeon’]. Neifalta-Lakūnas, commander of the Kalniškės area partisans, was deputy to Kisieliauskas- Karvelis and the head of the command post. The composition and organisational structure of the force was the same as many other Lithuanian partisan forces. The detachment adopted the structural principles of the independent Lithuanian Army and tailored them to the needs of the guerrilla war. In order to ensure confidentiality, separate smaller groups operated in different areas. These smaller groups were usually made from smaller mobile units formed from men of adjacent villages, and were lead by fighters with experience in the army or police service. From the beginning of the Soviet occupation, this partisan company was trying to unite itself into a centralised resistance movement. Initially a relationship was established with the Lithuanian Freedom Army, and 2 new units – Tauras and Dainava Commands – emerged as a result of this centralisation. The creation of centralised underground structures legitimised the activities of the partisan force. The release of proclamations and regulatory documents by the leadership formed the concept of anti-Soviet resistance, regulated its tactics, discipline and behaviour with the civilian population. However, the chain of subordination was on many occasions disrupted and changed, while orders from command headquarters did not always reach the distant Kalniškės Forest. From February 1945 to March 1945, as far as mobility was concerned, the forces under the leadership of Karvelis and Lakūnas stood out from the rest of the partisan divisions operating in the ethnographic area of Užnemunės Dzūkija [south-western part of Lithuania]. The area of operations of this partisan force, which was extremely mobile and frequently changed its campsite, covered as many as seven rural areas. In the winter of 1944–1945 and spring 1945, up until the famous Kalniškės Battle, these fighters participated in many clashes with the occupational forces, but managed to avoid any major losses. Perhaps one of the most significant of these was the attack on the town of Rudamina and the skirmish at Panara. In both cases the partisans won, believed in the power of their weapons, and did not hesitate to initiate the Battle of Kalniškės. The Battle of Kalniškės was one of many defensive combats fought by partisans in 1945. It started when the NKVD Regiment surrounded the company of Neifalta- Lakūnas camping in the forest. The progress of the battle can be divided into four stages. During the battle partisans could not withdraw in an organised fashion and had to fight the enemy attacks on Meškakalnis hill. Some fighters were cut off from the main division and were scattered to the depths of the forest. After intensive fire, partisan resistance weakened. The NKVD assault group tried to push the partisans from their occupied positions and to completely destroy them, but around 20 men managed to break out of the encirclement. Although the Battle of Kalniškės claimed the lives of nearly 50 partisans, their dedication inspired their brothers in arms, kept the movement smouldering in the nation’s consciousness, and lead to the re-establishment of Lithuania’s independence.